Principal features of Chornohora climate (Ukrainian Carpathians) - Błażejczyk, Krzysztof; Skrynyk, Oleh (Bulletin of Geography. Physical Geography Series, 2019)
Chornohora is the highest mountain ridge in the Ukrainian Carpathians with 6 peaks of an altitude over 2,000 m above sea level (Hoverla is the highest peak, 2,061 m a.s.l). its climate is explored less than other mountain ridges in Europe. The massif is a climatic barrier for air masses on NW-SE line. To describe the climate of this area data from the weather station at Pozhyzhevska alpine meadow for the years 1961-2010 were used. The seasonal and long-term variability of air temperature, atmospheric precipitation and snow cover were investigated on the background of air circulation types. The results show that general features of Chornohora climate depend both, on elevation above sea level and on air circulation. Lowest temperature is observed at N-NE circulation and highest precipitation – at western air inflow. Long-term changes of examined climate elements in Chornohora show significant increase in mean (0.13°/10 years) and minimum (0.22°C/10 years) air temperature as well as in snow cover depth and number of snowy days.